Economic Implications of the Corona Crisis and Economic Policy Measures - Peter Bofinger; Sebastian Dullien; Gabriel Felbermayr; Clemens Fuest; Michael Hüther; Jens Südekum; Beatrice Weder di Mauro (Wirtschaftsdienst)
Abstract The corona crisis started in China and had great consequences for public health and the economy. In the meantime, high and rapidly growing numbers of cases of infections with SARS-CoV-2 have also been recorded in Japan, Korea, Italy, Germany, Great Britain, France, Spain and above all in the USA. Forecasts of economic growth have been massively revised downwards and governments around the world are struggling to find the right economic policy response. This article describes basic short-term options for the German government to react to the corona shock and briefl y assesses the package of measures “Schutzschirm für Beschäftigte und Unternehmen” presented on 13 March 2020 by the German Finance Minister Olaf Scholz and the German Economics Minister Peter Altmaier.